A practitioner-focused approach to the provision of psychological support in soccer: Adopting action research themes and processes - Gilbourne, D.; Richardson, D. (Journal of Sports Sciences, 2005)
In this review, we explore a practitioner-focused approach to the provision of psychological support in soccer. Support is depicted to be a collaborative exercise and is associated with action research themes and processes. Various procedures and perspectives that are associated with action research are outlined. The ideas presented suggest that many soccer-based practitioners (coaches, managers and physiotherapists) have the capacity to influence how sport psychology practice might be experienced by players. The sport scientist is depicted here as someone who acts as a critical friend to those practitioners who are interested in developing aspects of their own working practice. Having established these ideas, the review provides an illustration of how a combination of action research themes and qualitative research techniques has been used to influence and support heads of education and welfare in UK soccer academies across the north-west of England.